Halal Cosmetics and Acne Vulgaris: Uncovering Consumer Behavior and Sustainable Solutions - Fatimah, Andini Nur; Hidayat, Arif; Setiadi, Adi; Juliana, Juliana; Marlina, Ropi; Umar, Abdurrauf (Universitas Pendidikan Indonesia, 2024)
Purpose – This study aims to analyze the factors that influence the behavior of Muslim consumers, especially students, in choosing halal cosmetics to treat acne vulgaris. This study also explores how halal awareness, information sources, education level, and family history influence purchasing decisions, as well as the contribution of halal cosmetics to the Sustainable Development Goals (SDGs). Design/methodology/approach – This study uses a quantitative descriptive approach. Data were collected through a survey using a questionnaire distributed online to 70 students. Respondents were selected using a purposive sampling technique. Data analysis was carried out using the Microsoft Excel method. Finding – The results showed that halal awareness is the main factor influencing the decision to purchase halal cosmetics (35%), followed by trusted sources of information, such as health workers (30%). The factor of family history with oily skin increases the tendency to choose halal products (60%). In addition, students with higher education levels (semesters 3-4) are more selective in choosing halal cosmetics (70%) compared to students in the early semesters (50%). The most frequently used product for acne vulgaris treatment is facial cleanser (83.87%).